Implementation of role-based access control, multi tenancy and audit logging in a single sign-on system - Aswintama, Putranta; Haryanto, Eri; Setyawan, Ryan Ari (Institute of Computer Science (IOCS), 2025)
As enterprises increasingly require centralized, secure, and efficient authentication mechanisms, Single Sign-On (SSO) has emerged as a strategic approach to managing user access. This study discusses the implementation of an SSO system based on Laravel Livewire with support from JSON Web Token (JWT) and OAuth, developed for PT Radiator Springs Indonesia. The system integrates three main components: Role-Based Access Control (RBAC) for access rights management, a Multi-Tenancy architecture for separating users across organizational units, and Audit Logging to track user activities. The analysis shows significant improvements in security, with 87.5% fewer unauthorized access attempts and enhanced user management efficiency, evidenced by a 71.43% reduction in time to onboard new users. Additionally, the system generates over 300+ audit log entries per day, improving monitoring and compliance capabilities.